Efficacy and Safety of SPRINT and STAR Protocol on Malaysian Critically-ill Patients - Nurhamim, Ahamad; Normy Norfiza, A. Razak; Ummu Kulthum, Jamaludin; Fatanah, Suhaimi; Christopher, Pretty; Geoffrey, Chase; Azrina, Ralib; Basri, Mohd Noor (IEEE, 2017)
Intensive care unit patients may have a better glycaemic management with the right control protocol. Results of virtual trial performance on Malaysian critically-ill patients adopting a model-derived and model-based control protocol known as SPRINT and STAR are presented in this paper. These ICU patients have been treated by intensive sliding-scale insulin infusion. The effectiveness and safety of glycaemic control are then analysed. Results showed that patient safety improved by 83% with SPRINT and STAR protocol as the number of hypoglycaemic patients significantly reduced (BG<;2.2 mmol/L). Percentage of time within desired bands and median BG improves in both SPRINT and STAR. However, the improvements are associated with higher number of BG measurements (workload).